Declassified satellite photographs and archaeology in the Middle East : case studies from Turkey - Kennedy, David
Recent availability of declassified satellite images of landscapes and ancient cities in Turkey offer new and valuable material for archaeolgical research. Here David Kennedy explains the significance and use of some images in the Euphrates Valley.